2022
DOI: 10.1186/s12913-022-08011-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of health professionals for oxygen therapy working in South Gondar zone hospitals, 2021: multicenter cross-sectional study

Abstract: Introduction Therapeutic oxygen should be administered by competent healthcare providers who possess the required competencies of knowledge, skill, and judgment/abilities to make clinical decisions regarding the administration of oxygen. Therefore, this study aimed to assess the knowledge, attitude, and practice of health professionals towards oxygen therapy. Methods A multicenter institutional-based cross-sectional study was conducted among 218 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Likewise, this is a considerable magnitude that can not just be ignored should oxygen therapy practices be improved in health facilities. A similar proportion (34.9%) was determined in Ethiopia [24] due to comparable sample size and measurements used, while a much higher proportion (67.0%) for the poor practice of supplemental oxygen administration was reported among nurses in the same country [15], with a possible reason being differences in the study settings as the level of health facility in our study was higher compared to that in Ethiopia. While the level of oxygen administration knowledge didn't predict the level of practice in our study, a study in Ethiopia demonstrated that nurses with good knowledge of supplemental oxygen administration were 12-times more likely to have a good practice of supplemental oxygen administration than those who had poor knowledge [15], which could still be explained by differences in settings.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Likewise, this is a considerable magnitude that can not just be ignored should oxygen therapy practices be improved in health facilities. A similar proportion (34.9%) was determined in Ethiopia [24] due to comparable sample size and measurements used, while a much higher proportion (67.0%) for the poor practice of supplemental oxygen administration was reported among nurses in the same country [15], with a possible reason being differences in the study settings as the level of health facility in our study was higher compared to that in Ethiopia. While the level of oxygen administration knowledge didn't predict the level of practice in our study, a study in Ethiopia demonstrated that nurses with good knowledge of supplemental oxygen administration were 12-times more likely to have a good practice of supplemental oxygen administration than those who had poor knowledge [15], which could still be explained by differences in settings.…”
Section: Discussionsupporting
confidence: 74%
“…The percentage score was calculated by summing up the number of responses from each respondent, divided by the total number of items assessed, and multiplied by 100%. As in a previous study [24], knowledge was categorized as good or poor based on the respondents' mean score which was used as a cut-off point. Therefore, respondents' knowledge above the mean score was considered as good and that below the mean score as poor knowledge.…”
Section: Measurementsmentioning
confidence: 99%
“…35 A study from Ethiopia found that good levels of KAP for OT administration were measured among half of their study participants, which included nurses, doctors and midwives. 36 A study from Saudi Arabia reported poor knowledge of OT indications among emergency health workers, and highlighted the potentially adverse impacts on patient outcomes. 37 There were no studies investigating the KAP of OT administration in the Pacific Islands.…”
Section: Introductionmentioning
confidence: 99%
“…High awareness of the potential risks associated with OT was found among both doctors (98%) and nurses (92.4%) in Iran 35 . A study from Ethiopia found that good levels of KAP for OT administration were measured among half of their study participants, which included nurses, doctors and midwives 36 . A study from Saudi Arabia reported poor knowledge of OT indications among emergency health workers, and highlighted the potentially adverse impacts on patient outcomes 37 .…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that although emergency department (ED) is one of the most important department responsible for treating patients in acute conditions [13], challenges such as the large number of emergency department visits, a variety of treatment methods, and time constraints to provide the best services may increase the risk of medical errors [17][18][19]. As a result, identifying the most common medical procedures and the educational requirements of the ED staff can play an important role in improving patient care, decreasing medical errors, and reducing the hospital stay time [3,14,20].…”
Section: Introductionmentioning
confidence: 99%